Novel aspects of taxifolin pharmacokinetics: Dose proportionality, cumulative effect, metabolism, microemulsion dosage forms - Lakeev, Alexander P.; Yanovskaya, Elena A.; Yanovsky, Vyacheslav A.; Frelikh, Galina A.; Andropov, Mikhail O. (Journal of pharmaceutical and biomedical analysis)
Taxifolin (TFL) is a small drug molecule with a broad therapeutic potential limited by its poor aqueous solubility and excessive metabolism. Despite comprehensive research, some aspects of the TFL pharmacokinetics, e.g., dose proportionality and possible cumulative effect, remain unexplored. In the current study, we have tried to fill this gap. Our results revealed that the TFL pharmacokinetics in rats had nonlinear character in the dose range of 10–50 mg/kg after its single oral administration (AUC). For Cmax, the data are ambiguous: linearity was confirmed via the equivalence criterion and was disproved using the power model approach. Also, the cumulative drug effect was observed on the 4th day after its multiple-dose oral administration (25 mg/kg; compared to the 1st day). Interestingly, biologically active TFL metabolites such as aromadendrin and luteolin were putatively found in plasma samples, although they were previously detected only in feces. In addition, oil-in-water and water-in-oil microemulsions were fabricated to design novel drug delivery systems. These carrier dosage forms did not improve the TFL bioavailability but significantly affected its metabolism. To support pharmacokinetic studies, the bioanalytical liquid chromatography–tandem mass spectrometry method was developed and validated in the concentration range of 1–1000 ng/mL using candesartan as an internal standard. Liquid-liquid extraction with methyl tert-butyl ether was used to isolate the analytes from plasma followed by evaporation and reconstitution of the residues in acetonitrile. Thus, the present findings broaden our understanding of the TFL behavior in vivo and provide novel ideas and reference directions for its continued use in medical practice.